Case Study: Topical Tribee Ointment Application with Moist Dressings in a Postoperative Diabetic Foot Ulcer Amputation Patient - Firmansyah, Andan; Hamdani, Dadi; Suhanda, Suhanda (LPPM STIKes Muhammadiyah Ciamis, 2025)
Diabetic foot ulcers are one of the most common and severe complications in patients with Diabetes Mellitus, often resulting in infections and amputations. Optimal wound care is crucial to accelerate healing and prevent further complications. a herbal ointment containing tea tree oil (Melaleuca alternifolia), vitamin E, and honey, has demonstrated antimicrobial, anti-inflammatory, and wound-healing properties. This case study aims to evaluate the effectiveness of topical Tribee ointment application using moist dressings in promoting wound healing in a postoperative diabetic ulcer amputation patient with a high risk of infection. This case study applied a nursing care process including assessment, diagnosis, intervention, implementation, and evaluation over four sessions with two-day intervals at the patient’s home. The nursing diagnosis was established using the Indonesian Nursing Diagnosis Standards (SDKI), with interventions guided by the Indonesian Nursing Intervention Standards (SIKI), and outcomes assessed through the Indonesian Nursing Outcome Standards (SLKI). The SOAPIER format was used for documentation. The patient was diagnosed with a high risk of infection (D.0142) related to post-amputation wounds. After receiving wound care with topical Tribee ointment and moist dressings for four sessions (30 minutes each), the patient's wound condition improved significantly, as measured by the Bates-Jensen Wound Status Continuum, with a score decrease from 35 to 28. Topical Tribee ointment combined with moist dressings is effective in enhancing wound healing in patients with diabetic foot ulcers, particularly those at high risk of infection.